Resposta dos manguezais do Sul da Bahia às mudanças climáticas e flutuações do nível do mar durante o holoceno: integração de dados polínicos e isotópicos com modelos de elevação digital - FIGUEIREDO, Beatriz Luna (Universidade Federal do Pará, 2018)
The objective of this work is to evaluate the extent of the impact of relative sea-level (RSL) rise during the early and middle Holocene and its subsequent fall during the late Holocene, as well as the influence of climate changes on mangrove and associated vegetation units along the Jucuruçu river valley in the southern state of Bahia, Northeast Brazil. This work integrates topographical, geomorphological, sedimentological, palynological and isotopic data of sediment cores sampled along this fluvial valley. The core PR8 with 7.5 m depth, positioned 37 km distant from the modern coastline, upstream of the Jucuruçu river, was used as reference to integrate the other cores. The data reveal three important facies associations characterized by: 1) Presence of a estuarine channel, when the river valleys were incised and filled with fluvial deposits, as recorded by the PR8 (760-700 cm) and PR7 (460 – 800 cm), which are characterized by fining upward sandy successions; 2) presence of an estuarine channel with tidal flats occupied by mangroves and herbaceous vegetation during the early and middle Holocene; 3) the third phase is characterized by a fluvial flood plain with expansion of palms and herbaceous vegetation. During this phase, mangroves migrated to the mouth of the Jucuruçu river. PR8, sampled from a flood plain at about 6.8 ± 0.8 m above the current RSL, reveals an estuarine influence with the presence of mangrove pollen (5-40%) between 700 cm (~ 7400 cal yr BP) and 450 cm depth (~ 5800 cal yr BP). The PR8 indicated absence of mangrove pollen during the last 5800 years. In addition, the influence of the climatic patterns proposed for the Holocene can be identified throughout the studied cores. Probably, the combined effects of SRL fluctuations caused the changes in vegetation and sedimentary organic matter identified in PR8 and other cores analyzed, with a highest RSL at about 5350 cal yr BP and 3.25 ± 0.8 m, and changes in fluvial discharge. The geomorphological and vegetation evolution described for PR8, as well as for other cores along the Jucuruçu valley and positioned topographically lower (PR7 - 5 m, PR10 – 1.5, PR11 – 0.5 m and PR12 – 0.5 m above RSL) are compatible with the Holocene RSL curves for the northeaster Brazilian littoral.